The architecture of the metacity: Land use change, patch dynamics and urban form in Chiang Mai, Thailand - Brian McGrath (2018)
© 2017 by the authors. This essay analyzes the spatial and temporal dynamics which have emerged from the rapid development of Chiang Mai, Thailand over the last four decades. Modern urbanization since the 1980s in the previously remote Chiang Mai-Lamphun Valley has coincided with digital and financial globalization, neo-liberal governance, and the articulation of a new geological era of the Anthropocene based on evidence of human induced climate change. This time frame serves as a lens to theorize the architecture of the “metacity”, a new urban form and new form of urban practice responding to the demands of global digital financial networks and neo-liberal trade policies, but grounded in the ecology and life worlds of particular localities. The metacity appears in Chiang Mai within the interstices of a particularly fragmented rural/urban mix within a self-organized rather than plan-controlled built environment. The entire valley has been the site of intensive inhabitation for centuries, and recently urbanized, yet is spatially heterogeneous, extensive and patchy rather than ordered, bounded and uniform. The resulting landscape is marked by a disjunction between a feudal wet-rice cultivation land tenure structure overlaid with a market-based typology of urban real estate products with little enforcement of land use controls. The essay begins with theorizing the form of the metacity, continues with a description of the Chiang Mai case study, and concludes with a general assessment of the need to create a new form of metacity urban practice. A metacity design practice would re-conceptualize urban theories and forms by inking architectural and ecological thinking with inclusive social practices, enhanced by new digitally-enhanced urban imaginaries and new representational tools of mapping, modeling and design.